Genomic evolution and virulence association of Clostridioides difficile sequence type 37 (ribotype 017) in China - Xingxing Xu; Yuo Luo; Huan Chen; Xiaojun Song; Qiao Bian; Xianjun Wang; Qian Liang; Jianhong Zhao; Chunhui Li; Guangzhong Song; Jun Yang; Lingli Sun; et al. (Emerging Microbes and Infections)
Clostridioides difficile sequence type (ST) 37 (ribotype 017) is one of the most prevalent genotypes circulating in China. However, its genomic evolution and virulence determinants were rarely explored. Whole-genome sequencing, phylogeographic and phylogenetic analyses were conducted for C. difficile ST37 isolates. The 325 ST37 genomes from six continents, including North America (n = 66), South America (n = 4), Oceania (n = 7), Africa (n = 9), Europe (n = 138) and Asia (n = 101), were clustered into six major lineages, with region-dependent distributions, harbouring an array of antibiotic-resistance genes. The ST37 strains from China were divided into four distinct sublineages, showing five importation times and international sources. Isolates associated with severe infections exhibited significantly higher toxin productions, tcdB mRNA levels, and sporulation capacities (P < 0.001). Kyoto Encyclopedia of Genes and Genomes analysis showed 10 metabolic pathways were significantly enriched in the mutations among isolates associated with severe CDI (P < 0.05). Gene mutations in glycometabolism, amino acid metabolism and biosynthesis virtually causing instability in protein activity were correlated positively to the transcription of tcdR and negatively to the expression of toxin repressor genes, ccpA and codY. In summary, our study firstly presented genomic insights into genetic characteristics and virulence association of C. difficile ST37 in China. Gene mutations in certain important metabolic pathways are associated with severe symptoms and correlated with higher virulence in C. difficile ST37 isolates.